Tinjauan Pengaruh Store Atmosphere, Experiental Marketing dan Persepsi Nilai Terhadap Loyalitas Konsumen dengan Kepuasan Konsumen Sebagai Variabel Intervening: Studi Kasus pada Teman Semeja Coffee & Space Pekalongan - Kusuma Putra, Rengga (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This research, titled "OVERVIEW OF THE INFLUENCE OF STORE ATMOSPHERE, EXPERIENTIAL MARKETING, AND VALUE PERCEPTIONS ON CONSUMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE" (Case Study at Teman Semeja Coffee & Space Pekalongan), aims to analyze the effects of store atmosphere, experiential marketing, and perceived value on consumer loyalty, with customer satisfaction as an intervening variable. Data were collected through questionnaires from a sample of 100 respondents using a non-probability sampling method and purposive sampling technique. The study utilized validity and reliability tests, classical assumption tests, hypothesis testing (t-test), determination coefficient, path analysis, and the Sobel test with IBM SPSS 20.0. The results show that the store atmosphere has no significant effect on consumer loyalty (tcount = 1.901 < ttable = 1.984; Sig. = 0.060 > 0.05). Experiential marketing also shows no significant effect on consumer loyalty (tcount = 0.089 < ttable = 1.984; Sig. = 0.929 > 0.05; direct effect < indirect effect). However, perceived value has a significant effect on consumer loyalty (tcount = 2.046 > ttable = 1.984; Sig. = 0.044 < 0.05). Regarding the indirect effects, store atmosphere significantly affects consumer loyalty through customer satisfaction (Sobel test: tcount = 9.745 > ttable = 1.984; Sab = 0.0029 < 0.05), as does experiential marketing (Sobel test: tcount = 17.054 > ttable = 1.984; Sab = 0.0028 < 0.05) and perceived value (Sobel test: tcount = 34.191 > ttable = 1.984; Sab = 0.0029 < 0.05). Additionally, customer satisfaction has a significant direct effect on consumer loyalty (tcount = 4.889 > ttable = 1.984; Sig. = 0.000 < 0.05).